Texture dependence of hydrogen diffusion in nanocrystalline nickel by atomistic simulations. (5th April 2018) - Mohammadzadeh, Roghayeh; Mohammadzadeh, Mina
Abstract: Atomistic simulations were performed to highlight the importance of the texture on the diffusion of hydrogen atoms in nanocrystalline nickel. Significant anisotropic diffusion is observed in longitudinal and through thickness directions. Our results show that the diffusion coefficient of hydrogen atoms through thickness in [001] textured nickel is larger than those values obtained for [011] and [111]. The diffusivity along longitudinal and transverse directions in [111] textured samples is found to be higher than that along thickness direction. Additionally, it is determined that the presence of hydrogen atoms changes the vacancy formation of the substrate and the vacancy defects are responsible for the anisotropy of hydrogen diffusion. These findings improve our understanding of hydrogen diffusivity at the atomistic level for hydrogen storage in the materials. Highlights: Dependence of hydrogen diffusion to the initial texture of nickel was investigated. Anisotropy of hydrogen diffusion in textured nanocrystalline nickel was observed. Diffusivity in [001] textured nickel was faster through thickness direction. Presence of the hydrogen atoms in the substrate induces the formation of vacancies.